Towards universal healthcare coverage through adoption of blockchain technology: a literature review - Mwashuma, Elizabeth Wanjala (Journal of Health Informatics in Africa, 2018)
Countries in low and middle income countries (LMICs) are embarking on a path to achieve universal healthcare coverage (UHC) for its populace. The growth is evidenced by the renewed commitment by governments, both from a policy and implementation perspective, to providing affordable healthcare for all of its citizens by increasing financial risk protection through the National Health Insurance Funds (NHIF), even adding more benefits targeting informal sector households and adjusting outpatient cover; to improve access to health and improve the national health outcomes. Despite these commendable efforts, there are still several challenges facing the health provision in LMICs. High poverty levels, increased unemployment rates, high cost of care, disparate information systems and weak data use culture, inadequate funding, inadequate tax collection system, corruption, weak management and oversight by regulator, insufficient skilled personnel and difficulties in identifying and reaching the most vulnerable citizens, are all challenges that have impacted negatively on health. The potential uses of blockchain technology in healthcare are multiple; blockchain technologies have advanced and have matured to hold the promise to unite the disparate processes in the pharmaceutical industry and healthcare ecosystem, reduce costs, improve regulatory compliance, increase data flow, and improve patient experience and outcomes. The objectives of this paper is to present a review of published articles and journals that discuss the applications of blockchain technology in healthcare in order to gain knowledge about methodologies used and findings obtained from the implementation of blockchain solutions in healthcare settings. Literature review included critical assessment of 19 papers to identify studies that examine the use case for blockchain technology in healthcare. The findings show that Blockchain proves to be key in building a global precision-medicine ecosystem that optimally connects patients, clinicians, researchers, insurers and clinical laboratories to one another. Blockchain can improve patient data security, data sharing, interoperability, patient engagement, big data analytics, health information exchange, fighting counterfeit drugs, R&D processes, AI-based diagnostics and fostering vertical business models. Other potential breakthroughs in the healthcare ecosystem are not limited to cost reduction, improve regulatory compliance, increase data flow, and improve patient experience and outcomes. Keywords: Blockchain, NHIF, UHC, LMICs, FHIR, smart contracts